Memes in Motion: A Semiotic Analysis of Student-Produced Memes for Italian as a Foreign Language - Bautista, Naidyl Isis; Guban-Caisido, Danica Anna (Universitas Muhammadiyah Yogyakarta, 2026)
Background: In FL classrooms, multimodal texts like memes offer a twofold benefit: they enhance students’ digital literacy and foster authentic engagement with the content. However, much of the previous research focused on grammar-focused FL courses rather than content-focused ones. Objective: The paper uniquely explores how memes can be leveraged as an engaging tool in FL content courses. Methods: Barthian semiotics was used to analyze memes produced by university students enrolled in Italian content courses to understand how they engaged with the academic content, disseminated their understanding, and navigated among semiotic elements to deliver effective and entertaining memes in the FL. Findings: Findings indicated that students used humor to highlight key concepts, carefully combining visual and textual elements to convey a nuanced understanding of the lessons. Humor functioned to clarify ideas while engaging peers, and memes functioned as social semiotic prompts that invited multiple interpretations. Conclusion: As a result, students used them to either strengthen or challenge the prevailing narrative. Future directions recommend integrating memes into FL pedagogy, whether for teaching pragmatics or intercultural awareness, as they promote both practical language competencies and collective, socially engaged learning.